USING THE INTEGRATING CONCEPT OF AUTOMOBILE IN TEACHING THE GENERAL TECHNICAL SUBJECT AT PRIMARY SCHOOL - MINARCIK, Josef; HAVELKA, Martin (Trends in education, 2009)
The article deals with some possible use of the LEGO construction set in teaching the general technical subject at primary school during teaching aimed at teaching the integrating topic of automobile. In the connection are among others suggested methods appropriate for realization the named teaching.
Keywords: automobile; construction kit; LEGO Education; project teaching.